Pengaruh Penerapan Media Digital dalam Pembelajaran terhadap Keaktifan dan Partisipasi Siswa Sekolah Dasar - Farhatun Haya; Khaira Nisa; Rio Febrian Ladipasa; Mutiara Ananda; Finda Rustiana; Muhammadi Muhammadi; Ranti Meizatri (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
The advancement of digital technology has transformed classroom learning practices. Digital learning materials provide an innovative approach to fostering more engaging and interactive learning environments. Student activeness and participation are key indicators of effective learning; however, traditional instructional methods are still widely used in elementary schools, often limiting student engagement. This study examines the relationship between the use of digital learning materials and student activeness and participation at SD Binekas using a quantitative descriptive correlational approach. Upper-grade elementary students were selected as research participants. Data were collected through structured observations, student participation instruments, and documentation, and analyzed using statistical techniques. The results demonstrate that digital learning materials have a positive and significant effect on student activeness and participation. Students showed higher levels of attention, interaction, and involvement during classroom activities. These findings highlight the potential of digital learning materials to support active and participatory learning in elementary education.